If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 4 = 3x + -5 Reorder the terms: 4 + x = 3x + -5 Reorder the terms: 4 + x = -5 + 3x Solving 4 + x = -5 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 4 + x + -3x = -5 + 3x + -3x Combine like terms: x + -3x = -2x 4 + -2x = -5 + 3x + -3x Combine like terms: 3x + -3x = 0 4 + -2x = -5 + 0 4 + -2x = -5 Add '-4' to each side of the equation. 4 + -4 + -2x = -5 + -4 Combine like terms: 4 + -4 = 0 0 + -2x = -5 + -4 -2x = -5 + -4 Combine like terms: -5 + -4 = -9 -2x = -9 Divide each side by '-2'. x = 4.5 Simplifying x = 4.5
| 7m-8m+2=3 | | 8(4u--1)-12u=11(2u-6) | | 2(x+4)=5(3x-7)-3(x+2) | | 7(2x-8)=8 | | 7y-2 | | -44-92=31-3z | | -4y+10=-2(3y+2) | | 20+x=7 | | (2x-9)+(1.5x+6)=32 | | ln(x)=2ln(3)+ln(5) | | 4(x-6)=3x+16 | | 2(x-1)-7x=18-5(x+4) | | 4=-2h+9 | | 2m=1 | | 4x+7=1x-2 | | 2(x-1)17x=18-5(x+4) | | 9(x-2)/3=27 | | .25(-x-8)=45 | | 5(x+-7)=-45 | | 2x+5-2x^2-3x= | | 7y-2(8+1)=4 | | x+r=9 | | 500-15w=200+12w | | 6-20=24 | | 5+4x=41x | | 6(x-4)=24-2x | | 5x+11=20+2x | | 10x-15=8x+14 | | -96-10x=9x+16 | | 2x-6=39-7x | | -a+(3a)+15+15a-(-2)= | | 4(x-6)-8=-32 |